CROSS-DISCIPLINARY APPROACH IN SCIENTIFIC INTEGRATION AND ITS APPLICATION IN ISLAMIC EDUCATION - Zen Ma'arif, M.; Naim, Ngainun; Akhyak (International Journal of Multidisciplinary Reseach, 2026)
This study aims to analyze the concept and application of the cross-disciplinary approach in Islamic education as a strategy to integrate Islamic values with modern scientific knowledge. The research employs a qualitative approach using library research, focusing on an in-depth examination of scholarly literature from journals, proceedings, and academic documents. The analysis follows three main stages: collecting relevant literature, evaluating its validity and relevance (Creswell, 2014), and conducting content analysis to explore themes of knowledge integration and Islamic epistemology (Zed, 2014). The findings reveal that the cross-disciplinary approach in Islamic education encompasses three main forms: instrumental, which utilizes methods or tools from other disciplines; conceptual, which fosters dialogue across disciplines to expand theoretical frameworks; and transformative, which seeks to create new paradigms through the integration of science and Islamic values. Its practical implementation can be observed in integrative curricula at Islamic universities (UIN), ethically grounded institutional management, and research based on maqashid al-shariah. This study concludes that the cross-disciplinary approach plays a crucial role in building holistic, contextual, and globally competitive Islamic education. It strengthens the epistemological foundation of Islamic scholarship by uniting spirituality, rationality, and professionalism into a coherent educational paradigm.